The Role of Personal Values in Forming Students’ Entrepreneurial Intentions in Developing Countries - Karimi, Saeid; Makreet, Ahmad Salman (Frontiers in Psychology, 2020)
The purpose of this study was to examine mechanisms through which personal values are associated with entrepreneurial intentions by integrating the theory of human values into the theory of planned behavior (TPB). Data were collected using a questionnaire from a sample of 452 agriculture students who were selected from two public universities in two Persian-speaking countries, namely Iran and Afghanistan. The results of structural equation modeling showed that individualistic personal values, that is, openness to change and self-enhancement values, are not directly related to entrepreneurial intentions. However, these personal values were indirectly related to entrepreneurial intentions through attitude toward entrepreneurship and perceived behavioral control. The results also showed no significant difference between the two countries in terms of the relationship between the personal values and three TPB anchors (i.e., attitude toward entrepreneurship, subjective norms, and perceived behavioral control) or the relationship between TPB anchors and entrepreneurial intentions. The study indicates how personal values play a role in explaining entrepreneurial intentions and establishes the utility of the TPB model in seeking a value–intention linkage in the field of entrepreneurship in developing countries. As a practical implication, the study suggests that educators of potential entrepreneurs should try to stimulate personal values more often because this fosters entrepreneurial intentions and their antecedents.